PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT VARTA MICROBATTERY INDONESIA - Nurrokhmah, Tiama Aulia; Wasiman, Wasiman (SCIENTIA JOURNAL, 2021)
This study goals for determine the effects of work stress and working environments on employee performance at PT. VARTA Microbattery. This research uses quantitative methods. Data obtained based on the answers of 199 questionnaire participants. The data that has been collecting will be analyze with the helps of SPSS version 25. The result showing that the coefficients of determination (R2) gave a value of 0.692. It is concluding that work stress and works environment has effects of 69.2% on the employee performances of PT. VARTA Microbattery and the remained 30.8% are influence by other variables which is not including as researches variables.